Improving the analytical toolbox to investigate copurifying host cell proteins presence: N‐(4)‐(β‐acetylglucosaminyl)‐ l‐asparaginase case study. Issue 11 (3rd August 2020) - Clavier, Séverine; Fougeron, Delphine; Petrovic, Suzana; Elmaleh, Hagit; Fourneaux, Céline; Bugnazet, Dawid; Duffieux, Francis; Masiero, Alessandro; Mitra‐Kaushik, Shibani; Genet, Bruno; Fromentin, Yann; Kreiss, Patrick; et al.
Abstract: Levels of host cell proteins (HCPs) in purification intermediates and drug substances (DS) of monoclonal antibodies (mAbs) must be carefully monitored for the production of safe and efficacious biotherapeutics. During the development of mAb1, an immunoglobulin G1 product, unexpected results generated with HCP Enzyme‐Linked Immunosorbent Assay (ELISA) kit triggered an investigation which led to the identification of a copurifying HCP called N ‐(4)‐(β‐acetylglucosaminyl)‐l ‐asparaginase (AGA, EC3.5.1.26) by liquid chromatography–tandem mass spectrometry (LC‐MS/MS). The risk assessment performed indicated a low immunogenicity risk for the copurifying HCP and an ad hoc stability study demonstrated no mAb glycan cleavage and thus no impact on product quality. Fractionation studies performed on polishing steps revealed that AGA was coeluted with the mAb. Very interestingly, the native digestion protocol implemented to go deeper in the MS–HCP profiling was found to be incompatible with correct AGA detection in last purification intermediate and DS, further suggesting a hitchhiking behavior of AGA. In silico surface characterization of AGA also supports this hypothesis. Finally, the combined support of HCP ELISA results and MS allowed process optimization and removal of this copurifying HCP. Abstract : During monoclonal antibody 1 development, unexpected results generated with host cell protein (HCP) Enzyme‐Linked Immunosorbent Assay (ELISA) kit triggered an investigation which led to the identification of a copurifying HCP called N ‐(4)‐(β‐acetylglucosaminyl)‐l ‐asparaginase by liquid chromatography–tandem mass spectrometry (LC‐MS/MS). To mitigate the risk and improve the HCP clearance, a multidisciplinary approach was successfully applied including product and patient risk evaluation, in silico HCP surface characterization, and in‐depth understanding of this HCP behavior during downstream purification process.